EFISIENSI BEBAN PAJAK PENGHASILAN BERDASARKAN PP No. 23/2018 PADA UMKM PEMULA DI PAMEKASAN - Ustman Ustman; Rika Syahadatina (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
This research was conducted in Pamekasan MSMEs due to the enactment of changes in tax regulations in 2018 for corporate taxpayers, namely the comparison of calculation, deposit, and reporting of corporate income tax (PPh) according to Law No. 36 of 2008 and Government Regulation No. 23 of 2018 on MSMEs with certain turnover. The purpose of this research is to calculate and compare the calculation, deposit, and reporting of corporate income tax (PPh) in accordance with the new regulations. In this study, the author uses a descriptive method, namely explaining the calculation and procedures for calculating corporate income tax (PPh) in accordance with applicable regulations. The results of this study, the author can create a scientific work that contains procedures for calculating, depositing, and reporting taxes in accordance with applicable regulations.